Transport Modeling and Leaching Kinetics in Groundwater of Shiwashok Oil field, Kurdistan Region, Iraq - Azad Taher Kareem; Rawaz Rostam Hamadamin; Omed Mustafa; Hawber Ata Karim; Mamoon Qadir Salih (Tikrit Journal of Pure Science)
Groundwater is one of the most important sources of water supply. Drinking safe water is vital for the health and well being of the community. To do this research, eight groundwater samples were collected from different sampling stations during the three sampling periods (January, May and July). The detected predominant cations are calcium and magnesium along with sulfate from the anions in most of the samples. Mean total dissolved solid of Darbasar Bchuk shows exceptionally high concentration levels compared to the other sampling sites, which is equal to 1193.3 mg/L. Due to concerns about the effects of oil production activities on groundwater quality in Shiwashok oil field, a one-dimensional transport modeling was simulated. The simulated data shows that the contaminants that reach the water wells have a high concentration compared to the detected concentrations of the contaminants in the wells. More time scale is required for the contaminant to reach the steady state or decrease to be lower than the permissible level. The O2 and NO3- reduction rates are slow as compared with the downward rate of water transport. CEC and organic matter in the groundwater are the main factors that govern the fate of transport of the contaminants.